The intellectual and aesthetic dimensions of pictorial drawings in the pottery of the Archaic age as an entry point for the creation of contemporary painting - Mona El tobgy (Journal of Architecture, Art & Humanistic Science, 2022)
The research deals with the study of the distinctive artistic features of pictorial drawings in the pottery of the historical age, and the intellectual and philosophical propositions that are associated with them, expressed by the artist and her body through various and studied topics. On which the artistic innovations of this era are based, the graphic drawings on the vessels of the historical era have acquired special features, characterized by simplicity and accuracy in drawing; It was characterized by vitality and movement free from monotony and stagnation, calm in colors and creativity in dealing with subjects that were characterized by fertile imagination, as the research dealt with the intellectual and aesthetic dimensions of the paintings of the Archaic era, where the drawings were linked to ideological thought and myths as well as they expressed topics depicting different scenes of life such as scenes of singing and music. Banquets, sports matches ... and others, The results of the theoretical study came to confirm the domination of mythological and doctrinal subjects over the artist’s imagination in the Archaic era in the Greek civilization. At the end of the research, a subjective experiment was applied for the researcher aimed at extracting the artistic features and aesthetic mysteries of the pictorial drawings on the surfaces of pottery as a source of artistic creativity in the field of photographic art. As well as the creation of contemporary pictorial works by drawing inspiration from the style and artistic features of pictorial drawings in pottery in the historical era, in line with the philosophy of contemporary art